2021
DOI: 10.1111/1440-1630.12750
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapy intervention for cancer patients following hospital discharge: How and when should we intervene? A systematic review

Abstract: Introduction Advances in cancer treatment over the last decade have led to increased survival rates. As a result, survivors are living longer with and beyond cancer, often with greater levels of morbidity. Occupational therapists, with their focus on remedial and compensatory strategies to improve function and participation, are well suited to assess and intervene with this population. Despite this, little research exists to demonstrate the efficacy of interventions and value of the occupational therapy role. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…To our knowledge, this is the first study to examine the role of AM-OT on opioid medication refills during the PAP after BCRS. While previous research has noted OT's efficacy for addressing functional, emotional, and biomechanical impairments following cancer treatment when implemented during the PAP (Taylor et al, 2021), novel findings of our study indicate that patients who received AM-OT had significantly fewer opioid medication refills during this same period. This directly supports the aims of CARA (Whitehouse, 2016).…”
Section: Discussioncontrasting
confidence: 69%
“…To our knowledge, this is the first study to examine the role of AM-OT on opioid medication refills during the PAP after BCRS. While previous research has noted OT's efficacy for addressing functional, emotional, and biomechanical impairments following cancer treatment when implemented during the PAP (Taylor et al, 2021), novel findings of our study indicate that patients who received AM-OT had significantly fewer opioid medication refills during this same period. This directly supports the aims of CARA (Whitehouse, 2016).…”
Section: Discussioncontrasting
confidence: 69%
“…Current evidence agrees with the need for further research in multidisciplinary oncology rehabilitation and recommends a multidisciplinary approach in patients with BCRL, including but not limited to occupational therapy [18][19][20][21][22][23][24][25], health training/promotion [9,[26][27][28] and physical activity [29,30].…”
Section: Introductionmentioning
confidence: 54%
“…Third, regarding feasibility of TERRA, adjustments made during the course of the programme to respect the needs of participants, such as extending breaks, were valuable for tailoring. Taylor et al [14] studied occupational interventions for cancer patients and indicated that monitored tailoring of intervention programmes might improve outcomes. Implementation was, however, hindered by the heterogeneity of the participants' RRTW phase as well as their illness phase.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%